What Has No Place, Remains: The Challenges for Indigenous Religious Freedom in Canada Today - Shrubsole, Nicholas (University of Toronto Press, 2019)
Frontmatter -- Contents -- Preface -- A Comment on Terminology -- Abbreviations -- Introduction -- 1. Al Purdy’s Modern Scepticism -- 2. Secularization, Dispossession, and Forced Deprivatization -- 3. Religions Plus? Competing Frameworks of Indigenous Religious Freedom -- 4. Dealing with Diversity Poorly and the Gustafsen Lake Standoff -- 5. The Duty to Consult and Accommodate -- 6. The Potential and Limits of International Mechanisms of Redress -- Conclusion. Challenges for Reconciliation -- Notes -- Bibliography -- Index